REGULATION OF RELATIONS BETWEEN THE CUSTOMER AND THE EXECUTOR OF THE STATE DEFENSE ORDER - E. V. Lyuter (Real Economics Publishing House, 2016)
Below is the original author's method of assessment of financial and economic sustainability of enterprises-performers of the state defense order. This method takes into account the financial and economic performance of the enterprise. The proposed comprehensive indicator of financial and economic sustainability can be used by the state customer at the stage of analyzing the possibility of the state contract execution by potential contractors.